The impact of private investment on economic growth: Iraq as a case study for the period (2004-2022) (Entrepreneurship Journal for Finance and Business, 2025)
Private investment is the cornerstone of building the economies of developed and developing countries by supporting productive activities and increasing economic growth and development. This research aims to identify the positive impact of the private sector on improving the Iraqi economy and increasing the gross domestic product (GDP), which is reflected in reduced unemployment and poverty, especially during years of financial and economic crises. Despite the problems facing the private sector and its low investment, it remains the primary driver of economic growth. Given the importance of the topic, the research aims to identify the impact of private investment on economic growth in Iraq for the period (2004-2022) using advanced standard methods and approaches, including unit root tests, cointegration, the error correction model (ECM), and the immediate response function. The study found a relationship between private investment and economic growth in the short term, and an inverse relationship in the long term.